Relationship between the prevalence of subclinical tenosynovitis and treatment in patients with RA in clinical remission: STARTER study. (6th September 2022) - Parisi, Simone; Zanetti, Anna; Carrara, Greta; Scirè, Carlo Alberto; Iagnocco, Annamaria; Filippou, Georgios; ,
Abstract: Objective: This study is a sub-analysis from the patient cohort of the STARTER (Sonographic Tenosynovitis Assessment in RheumaToid arthritis patiEnts in Remission) study. The aim was to evaluate differences in ultrasound-detected joint and/or tendon involvement between patients receiving therapies based on a combination of conventional synthetic DMARDs (csDMARDs) and biologic DMARDs (bDMARDs) and those who were treated with either csDMARDs or bDMARDs in monotherapy. Material and methods: Four hundred and twenty-seven consecutive patients with a diagnosis of RA were recruited between October 2013 and June 2014. They were divided into three subgroups based on their therapy at baseline: patients with bDMARD in monotherapy, patients with csDMARD in monotherapy and patients in combination therapy (csDMARD + bDMARD). At baseline, 6 months and 12 months, a clinical examination (28 joint count) and an ultrasound evaluation were performed in each patient. A score of grey-scale (GS) and power Doppler (PD) synovitis and tenosynovitis was calculated based on the OMERACT scoring systems. Results: Two hundred and fifty-six patients completed the observation period: 48 patients from the bDMARD group (18.75%), 152 patients from the csDMARD group (59.38%) and 56 patients from csDMARD + bDMARD group (21.88%). The analysis showed that GS tenosynovitis and PD tenosynovitis are better controlled in combination therapy than they are with csDMARD alone ( P = 0.025 and P = 0.047, respectively); for PD synovitis, there was a better response in those who were treated with the combination therapy when compared with the patients receiving csDMARD ( P = 0.01) or bDMARD ( P = 0.02) alone. Conclusions: The analysis showed a lower prevalence of subclinical inflammatory manifestations detected with ultrasound imaging in those patients treated with the combination therapy than in those in monotherapy.